2015
DOI: 10.1214/15-ejs1089
|View full text |Cite
|
Sign up to set email alerts
|

Log-location-scale-log-concave distributions for survival and reliability analysis

Abstract: Abstract:We consider a novel sub-class of log-location-scale models for survival and reliability data formed by restricting the density of the underlying location-scale distribution to be log-concave. These models display a number of attractive properties. We particularly explore the shapes of the hazard functions of these, LLSLC, models. A relatively elegant, if partial, theory of hazard shape arises under a further minor constraint on the hazard function of the underlying log-concave distribution. Perhaps th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…It can be shown that the APGW distribution retains membership of the log‐location–scale–log‐concave family of distributions of Jones and Noufaily () and therefore, inter alia , unimodality of densities. We also now note, for future reference, the attractive form of the quantile function that is associated with H A , namely, Q A ( u )=[ H A {− log (1− u );1,1/ κ }] 1/ γ ≡ Q A1 ( u ; κ ) 1/ γ .…”
Section: The Specific Model For H0mentioning
confidence: 99%
See 2 more Smart Citations
“…It can be shown that the APGW distribution retains membership of the log‐location–scale–log‐concave family of distributions of Jones and Noufaily () and therefore, inter alia , unimodality of densities. We also now note, for future reference, the attractive form of the quantile function that is associated with H A , namely, Q A ( u )=[ H A {− log (1− u );1,1/ κ }] 1/ γ ≡ Q A1 ( u ; κ ) 1/ γ .…”
Section: The Specific Model For H0mentioning
confidence: 99%
“…Note that the Gompertz hazard function, h A .t; γ = 1, κ = ∞/ = exp.t/, including both vertical and horizontal scaling parameters, is λφ exp.φt/, and this can be reparameterized as λ Å exp.φt/ to arrive at the familiar form due to Gompertz (1825); see the on-line supplementary material for more Gompertz-related discussion. It can be shown that the APGW distribution retains membership of the log-location-scalelog-concave family of distributions of Jones and Noufaily (2015) and therefore, inter alia, unimodality of densities. We also now note, for future reference, the attractive form of the quantile function that is associated with H A , namely,…”
Section: Basic Definition and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Transforming the location-scale distribution using X = log(Y ) in which Y = e x produces a log-location-scale distribution. Based on this transformation, the location parameter µ becomes θ = e µ and the scale parameter σ becomes λ = 1/σ where θ is called the scale parameter and λ is called the power parameter [71].…”
Section: Location-scale and Log Location-scale Distributionmentioning
confidence: 99%
“…The PGW distribution was first introduced by Bagdonaviçius and Nikulin 7 (see also Nikulin and Haghighi 8 ), independently re-introduced by Dimitrakopoulou et al., 9 and recognized as an interesting competitor to the GG and EW distributions in Jones and Noufaily. 10…”
Section: Univariate Backgroundmentioning
confidence: 99%